PENGARUH BUDAYA KERJA DAN PEMBINAAN SUMBER DAYA MANUSIA TERHADAP KUALITAS KERJA PEGAWAI PADA PT. ANGKASA PURA - Andarias Sambo; Patuanta Agum Gumilang Rambe (Aliansi : Jurnal Manajemen dan Bisnis, 2019)
Human resource in a company to hold part of vital importance because the character as wisdom executor subject and operational activity companies good for progress company. work culture related to dominant values that is overspreaded insides organization as employee work philosophy, employee work quality threatens in human resource quality. with this employee development existence can memengaruhi labour capacity, so that will increase productivity and employee work quality concerned, which is on final can achieve aim that at specify previous punctually. This problem formulation : 1) What found work culture influence towards official work quality in PT. Angkasa Pura?; 2) What found human resource construction influence towards official work quality in PT. Angkasa Pura?; 3) What found work culture influence and human resource construction according to together towards official work quality in PT. Angkasa Pura?. This watchfulness aim: 1) To detect work culture influence towards official work quality in PT. Angkasa Pura. 2) To detect human resource construction influence towards official work quality in PT. Angkasa Pura. 3) To detect work culture influence and human resource construction according to together towards official work quality in PT. Angkasa Pura. Conclusion: 1) Found influence significant and positive between work culture towards official work quality in pt. balinese temple sky. this matter is this shows that when does work culture increase, so official work quality in PT. Angkasa Pura also increase balinese temple sky or on the contrary. With dimension culture function, characteristics and attitude. 2) Found influence significant and positive between human resource construction towards official work quality in pt. balinese temple sky. This matter is this shows that when does human resource construction increase, so official work quality in PT. Angkasa Pura also increase balinese temple sky or on the contrary. With dimension  know-how, work execution technique and inci. 3) Found positive influence and significant work culture and human resource construction according to together towards official work quality in pt. sky. this matter shows that according to together work culture and human resource construction can increase official work quality in PT. Angkasa Pura. With dimension ability, creativity and need.